PENGARUH DOSIS PUPUK KOMPOSIT TERHADAP PERTUMBUHAN DAN HASIL SORGHUM (Sorghum bicolor L Moench) DI TANAMAN VERTISOL - Wiyono Wiyono; Sri Rejeki Agustinah (JURNAL ILMIAH AGRINECA, 2017)
Sorgum is currently a commodity that is a government program in food diversification in Indonesia because it includes the most potential as a substitution of rice. In addition to its equivalent nutritional content of rice also has the advantage of being able to grow in a hot environment, less fertile, and limited water and even sandy land (Yanuwar, 2002, Sirrapa, 2003). Sorgum is needed by consumers with special needs other than because glutenous free food, low glycemic index (Sungkono et al., 2009). The development of the sorghum plant is the main alternative that needs to be pursued to meet the increasing demand for food while fertile land is decreasing. The purpose of this study was to determine the effect of composite fertilizer dosage on growth and Sorgum yield on Vertisol soil. This study used a Completely Randomized Block Design (RAKL) with 6 fertilizer doses (0, 40, 60, 80, 100, 120kg / ha NPK Ponska). This research was conducted on Vertisol soil in Sukoharjo regency. The results showed that the dose of Composite fertilizer had significant effect on growth and yield and Sorgum sugar level, but did not affect the weight of 1000 seeds. Composite Dosage 60 kg / ha is the highest dose that can be given to Vertisol Sukoharjo soil to increase the highest yield of Sorgum seed.